Food Safety Risk Analysis in East African Community: A Cornerstone for an Effective Regional Risk-Based Food Safety System - Hagenimana, Theoneste; Hategekimana, Jean Paul; Ooko Abong, George; Kamana, Olivier; Oswald Athanasia, Matemu (American Journal of Food Sciences and Nutrition, 2023)
Food risk analysis remains a major cornerstone that provides a framework for the risk-based food safety system. This paper aimed at evaluating the effectiveness of the food safety system, and the foundational role and opportunities of the risk analysis concept in the East Africa Community (EAC). The study was done through the explorative review of the literature as the best approach to getting broad information on the concept of risk analysis in global food safety and its impact on food safety systems. Through analysis of the relevant literature and previous studies related to global food safety and food safety systems, the approach helped to draw on challenges and opportunities and to reformulate the potential key role of the risk analysis concept in the EAC food safety system. Challenges were identified through the evaluation of the effectiveness of the EAC food safety system with reference to the US- effective food safety model. The role and opportunities of the risk analysis in the EAC food safety system were evaluated against identified challenges, and its implementation feasibility and assets in the EAC food safety system. As results, the EAC food safety system showed many gaps and challenges, and was ineffective. While the risk analysis concept was found a key factor in attributes of the effective food safety system, it could help the EAC food safety system to become effective, and to respond to the current and future food safety needs of both the African continent and the Globe. With many opportunities and potentials in EAC, the risk analysis concept can be integrated into the EAC food safety system. Therefore, a useful and strategic approach as a model of the integration of the risk analysis concept was designed for EAC. It is the establishment of an EAC- Regional Centre of Expertise in Food Risk Analysis (EAC-CREFRA). In addition, the EAC food safety system needs to anchor One Health and multi-factorial food safety management approaches to food safety.